The growing concern of chlorpyrifos exposures on human and environmental health - Nandi, Nilay Kumar; Vyas, Akshun; Akhtar, Md Jawaid; Kumar, Bhupinder (Pesticide biochemistry and physiology, 2022)
Chlorpyrifos (CP) and its highly electrophilic intermediates are principal toxic metabolites. The active form of CP i.e. chlorpyrifos oxon (CP-oxon) is responsible for both the insecticidal activity and is also of greater risk when present in the atmosphere. Thus, the combined effects of both CP, CP-oxan, and other metabolites enhance our understanding of the safety and risk of the insecticide CP. They cause major toxicities such as AChE inhibition, oxidative stress, and endocrine disruption. Further, it can have adverse hematological, musculoskeletal, renal, ocular, and dermal effects. Excessive use of this compound results in poisoning and potentially kills a non-target species upon exposure including humans. Several examples of reactive metabolites toxicities on plants, aquatic life, and soil are presented herein. The review covers the general overview on reactive metabolites of CP, chemistry and their mechanism through toxic effects on humans as well as on the environment. Considerable progress has been made in the replacement or alternative to CP. The different strategies including antidote mechanisms for the prevention and treatment of CP poisoning are discussed in this review. The approach analyses also the active metabolites for the pesticide activity and thus it becomes more important to know the pesticide and toxicity dose of CP as much as possible. [Display omitted] •Chlorpyrifos and its electrophilic intermediates are highly toxic metabolites.•The degradation of chlorpyrifos mainly involves the oxidation, hydrolysis and diarylation.•The reactive metabolites induce toxicities via oxidative stress, AChE inhibition, and endocrine disruption.•The degradation products were toxic on humans, plants, aquatic life, and soil.•The different treatment strategies including antidote mechanism alleviates the symptoms of poisoning.